POLA KETAHANAN (RESISTEN) DAN KEPEKAAN (SENSITIVITAS) KUMAN TERHADAP ANTIMIKROBA - Y F Tallulembang; Nurhayana Sennang; Benny Rusli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
In the developing countries including Indonesia, there still have problems with infectious diseases. Generally the hospitalized patientsin the Surgery section through have antimicrobial therapy. The treatment is intended to prevent nosocomial infection that usually foundin overnight treatment patients at the department of surgery. This study is carried out to know the pattern of micro-organism’s resistanceand sensitivity against various antimicrobial at department of surgery, Dr. Wahidin Sudirohusodo Hospital Makassar, January–June2008. A descriptive study of retrospectively collective data was carried out on 160 specimens by sensitivity test at the department ofsurgery, Dr. Wahidin Sudirohusodo Makassar Hospital, started from January up to June 2008. The five common bacterial found in thisstudy where Staphylococcus epidermidis, Klebsiella pneumonia, Enterobacter agglomerans, Staphylococcus saprophytic and Escherichiacoli. The sensitive antimicrobial drugs found where Vancomicin, Sulbactam/Cepoperazone, Cefepim, Gentamicin, Ceftazidim, Novobiocin,followed by the resistance antimicrobial were Methicillin, Tetracycline, Cefuroxim, Erythromycin, and Doxyciclin. The most bacterial typefound was Klebsiella pneumoniae, the most sensitive antimicrobial was Vancomicin and the most resistances were Methicillin.